ARI updates 2008: Accounting Research Institute and Faculty of Accountancy - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2008)
My sincere appreciation goes to all members of the Accounting Research Institute for the successful publication of this ARI Updates 2008. The institute had gone through a complete evolutionary cycle. When ITM was upgraded to UiTM in August 1999, research activities at the Faculty of Accountancy were confined to individual efforts. In early 2000, lecturers got together to form special interest groups (SIGs). In 2002, as the groups got bigger, an informal Accounting Research Academy (ARA) was formed and ARA was placed under the responsibility of the Deputy Dean (Quality and Research). Three SIGs, namely the Financial Reporting Research group, the Corporate Governance Research group and the Management Accounting Research group were later upgraded to research centres. Financial Reporting Research Centre (FRRC) was a collaboration with ACCA; Corporate Governance Research Centre (CGRC) was a collaboration with the Malaysian Institute of Corporate Governance- MICG and the Asian Management Accounting Research Centre (AMARC) was a collaboration with CIMA. The formation of these centres had further expedited research and publication activities at the faculty.